Combined effect of temperature and copper pollution on soil bacterial community: climate change and regional variation aspects - Henriques, Isabel
The aim of this study was to assess the combined effects of temperature and copper (Cu) contamination in the structure of soil bacterial community. For this, contaminated or spiked and control soils from two different geographic origins (PT-Portugal and DK-Denmark) were used. The DK soil was from a historically contaminated study field, representing a long-term exposure to Cu while the PT soil was from a clean site and freshly spiked with Cu. Soil bacterial communities were exposed in mesocosms during 84 days to 3 different temperatures based on values typically found in each geographic region and temperature conditions that simulated a warming scenario. Obtained results indicate that Cu stress alters the structure of bacterial community and that this effect is, to some extent, temperature-dependent. Effects on bacterial diversity for both soils were also observed. Differences in the DK and PT communities' response were apparent, with the community from the historically contaminated soil being more resilient to temperature fluctuations. This study presents evidence to support the hypothesis that temperature alters the effect of metals on soils. Further, our results suggest that the definition of soils quality criteria must be based on studies performed under temperatures selected for the specific geographic region. Studies taking into account temperature changes are needed to model and predict risks, this is important to e.g. future adjustments of the maximum permissible levels for soil metal contamination.